2022
DOI: 10.22331/q-2022-01-20-625
|View full text |Cite
|
Sign up to set email alerts
|

Faster quantum and classical SDP approximations for quadratic binary optimization

Abstract: We give a quantum speedup for solving the canonical semidefinite programming relaxation for binary quadratic optimization. This class of relaxations for combinatorial optimization has so far eluded quantum speedups. Our methods combine ideas from quantum Gibbs sampling and matrix exponent updates. A de-quantization of the algorithm also leads to a faster classical solver. For generic instances, our quantum solver gives a nearly quadratic speedup over state-of-the-art algorithms. Such instances include approxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Different possibilities are suggested by quantum algorithms for semidefinite programming [36], which can offer significant speedup over the current classical solution but require fault-tolerant quantum hardware. Authors in [37] have shown how to formulate semidefinite relaxations of QUBO problems.…”
Section: Combinatorial Optimization Techniques On Quantum Computersmentioning
confidence: 99%
“…Different possibilities are suggested by quantum algorithms for semidefinite programming [36], which can offer significant speedup over the current classical solution but require fault-tolerant quantum hardware. Authors in [37] have shown how to formulate semidefinite relaxations of QUBO problems.…”
Section: Combinatorial Optimization Techniques On Quantum Computersmentioning
confidence: 99%
“…Both algorithms demand a number of qubits linearly proportional to the problem's dimension, which poses challenges for solving large-scale QCQPs. Besides variational quantum algorithms, there is also a quantum algorithm based on a classical approximation algorithm called semi-definite relaxation [10]. This approach involves solving a semi-definite program as an approximation of the original QUBO problem, employing the quantum Gibbs sampling algorithm [11].…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquity of optimization problems across disciplines and the incredible computational resources they consume continues to motivate researchers to explore new and more efficient approaches to tackle them. Though quantum computing has so far offered limited provable computational advantages for combinatorial optimization problems [1][2][3][4][5][6][7][8][9][10][11][12][13][14], we expect that the library of quantum approaches for tackling different classes of optimization problems will expand as quantum information processors mature and become more readily available.…”
Section: Introductionmentioning
confidence: 99%